Pendidikan Karakter melalui Kitab Ta'limul Muta'alim di Pesantren Annajiyah 2 Tambak Beras Jombang: Studi Kasus tentang Pembentukan Akhlak Santri - Muhammad Faza Azka; Rofiatul Hosna (ANWARUL, 2025)
Character education through classical Islamic texts is a fundamental approach within the traditional pesantren education system. This study aims to explore the contribution of Ta’limul Muta’allim instruction to the moral development of students at Pondok Pesantren Annajiyah 2 Tambak Beras, Jombang, while addressing the challenges of character formation in the contemporary era. A descriptive qualitative approach was employed using a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving kyai, ustadz, and students across various educational levels. The findings reveal that traditional pesantren learning methods particularly bandongan and sorogan effectively internalize five core values of character education: sincere intention (niat ikhlas), respect for teachers, discipline and consistency, simplicity in lifestyle, and reliance on God (tawakal). These results affirm that pesantren-based character education demonstrates resilience in addressing the moral development of the younger generation, introducing the concept of transformative traditional learning as an alternative framework rooted in indigenous values. However, this study is limited by its single-site scope and cross-sectional design; thus, longitudinal and multi-site research is recommended to assess the long-term impact and broader applicability of pesantren-based character education within diverse educational contexts.